(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The article introduces the thematic dossier organized to reveal up-to-date studies on the issue of theatrical spaces, cities, and the different artistic experiences that take place in public and semi-public urban spaces of small and large locations. The themes extend from Maranhão to Rio Grande do Sul but also include the cities of Lisbon and Barcelona, demonstrating the multiple possibilities of the space for the performing arts.